Telerehabilitation for older people using off-the-shelf applications: acceptability and feasibility. (October 2014) - Crotty, Maria; Killington, Maggie; van den Berg, Maayken; Morris, Claire; Taylor, Alan; Carati, Colin
We investigated the feasibility of providing telerehabilitation in the home as an alternative to conventional ambulatory rehabilitation. Two groups of patients were accepted for telerehabilitation. The first group were community patients who needed rehabilitation, e.g. following a stroke, a fracture or prolonged hospital admission. The second group was from two rural nursing homes where residents were identified with a recent injury, fall or hospitalisation. Telerehabilitation employed a coaching model, with fewer therapist home visits, more feedback and "homework" for the patient. Patients had a tablet computer loaded with a videoconferencing app to connect with therapists and relevant therapeutic apps. Multidisciplinary care was provided for up to 8 weeks. The majority (86%) of eligible patients consented to receive telerehabilitation in their own home (n = 61) or in the country nursing home where they lived (n = 17). Most services were delivered using the 3G and 4G wireless networks with few technical problems. On average participants felt that they had achieved 75% of the goals set at the beginning of the programme. High levels of satisfaction were recorded. There was a 50% reduction in home visits by staff, or 10 visits per patient. Speech therapists were able to double occasions of service and direct patient contact time, whilst halving their travel time. Previous experience with technology and age were not barriers to this method of delivery but did affect recruitment. Telerehabilitation using off-the-shelf technology is feasible for post-acute treatment.